Canine and feline pregnancy loss due to viral and non-infectious causes : a review. - J., Verstegen; Dhaliwal, Gurmeet Kaur; Verstegen-Onclin, K. M. (Elsevier Inc., 2008)
Among the causes for pregnancy loss, viruses and non-infectious factors are among the most important. In both dogs and cats, research and clinical evidence provide proof that there is an increasing incidence of pregnancy loss associated with infectious diseases like herpesvirus, as well as the presence of toxicants or chemicals in the animal's diet and environment. Endocrine causes must be taken into consideration when dealing with pregnancy loss. This review will cover the most recent knowledge regarding viral and non-infectious of pregnancy losses in the dog and cat.